Blood Glucose Level and Pancreas Histological Section of Male Rabbits after Being Fed Commercial Feed Supplemented with Cod Liver Oil - Ni Gusti Ayu Manik Ermayanti; Ida Bagus Made Suaskara; I Gusti Ayu Manik Widhyastini; Iriani Setyawati (Universitas Nusa Bangsa, 2023)
Fish oil contains eicosapentaenoic acid (E.P.A.) and docosahexaenoic acid (D.H.A.) which are beneficial for heart health, controlling blood glucose, reducing atherosclerosis, and lowering the risk of cancer. This study aims to determine the effect of commercial feed supplemented with cod liver oil on blood glucose levels and pancreatic histology of male rabbits. Twenty rabbits were divided into four groups, namely commercial feed supplemented with cod liver oil 3% (P1), 4.5% (P2), 6% (P3), and commercial feed without cod liver oil supplementation (control). Each group consisted of five rabbits, and the treatment was given for four weeks. The parameters observed were blood glucose levels in the 1st, 2nd, 3rd, 4th, and 5th weeks and the histology of the male rabbitsâ€™ pancreas. Data were analyzed by Anova. The results showed that in the 1st, 2nd, and 3rd weeks there was no significant difference (P>0.05). In contrast, in the 4th Â and 5th weeks, there was a significant difference (P<0.05) between the control and treatment of cod liver oil supplementation on blood glucose levels in male rabbits, and the observational results on the histology of rabbits showed normal pancreatic histology. In conclusion, cod liver oil supplementation on commercial feed controlled blood glucose levels, and there was no disturbance in the histological structure of the pancreas of male rabbits.Keywords: fatty acid, glucose, cod liver oil, pancreas, rabbit